1963
DOI: 10.1084/jem.118.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Disease in the Adult Rat, a Model for Autoimmune Disease

Abstract: The cutaneous lesions of adult rats with homologous disease are described, and evidence is presented to indicate that they have an immunologic basis. The skin changes included erythema, purpura, edema, and a variety of inflammatory lesions. In the more active lesions, dermal infiltration, hydropic degeneration, acanthosis, and atrophy of the epidermis with hyperkeratosis and follicular plugging were present. In some cases, ulceration and sloughing were also observed. More chronic lesions were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…When allogeneic disease is induced in parent-* Fi hybrid strain combina tions, it is considered to serve as an experimental model for autoimmune disease in man (15,35,48). There are, however, differences concerning the nature of the antigen and the immunological status of tire host between the experiments described here and the two former instances just mentioned.…”
Section: Discussionmentioning
confidence: 91%
“…When allogeneic disease is induced in parent-* Fi hybrid strain combina tions, it is considered to serve as an experimental model for autoimmune disease in man (15,35,48). There are, however, differences concerning the nature of the antigen and the immunological status of tire host between the experiments described here and the two former instances just mentioned.…”
Section: Discussionmentioning
confidence: 91%
“…Prior to the identification of lymphocyte subsets, experiments in rats had demonstrated that the injection of immunogically competent cells into newborns, F1 hybrids, irradiated recipients or tolerized adults could induce a condition termed homologous disease characterized by features resembling human connective tissue disease [1][2][3][4][5][6]. It was subsequently shown in mice that the transfer of homozygous parental strain lymphocytes into normal F1 recipients induced a graft-vs.-host disease (GVHD), which resembled homologous disease in rats.…”
Section: A Introductionmentioning
confidence: 99%
“…Anti-PSS patients (2)(3)(4)(5)(6)(7)(8)(9)(10)29). In rats with graft-versus-host disease, Stastny et al (30) have observed sclerodermalike changes in the skin. A recent indication of the participation of abnormal cellular immunity in PSS has been furnished by Currie et al (31), who observed that lymphocytes from PSS patients with myositis produced cytopathic alterations in fibroblast cultures.…”
Section: Introductionmentioning
confidence: 99%